A micromechanical study of porous composites under longitudinal shear and transverse normal loading. (July 2015) - Ashouri Vajari, Danial
Abstract: The mechanical response of porous unidirectional composites under transverse normal and longitudinal shear loading is studied using the finite element analysis. The 3D model includes discrete and random distribution of fibers and voids. The micromechanical failure mechanisms are taken into account by considering the mixed-mode interfacial debonding and pressure-dependent yielding of the matrix using the modified Drucker–Prager plasticity model. The effect of the micromechanical features on the overall response of composite is discussed with a focus on the effect of microvoids and interfacial toughness. Finally, the computational prediction of the porous composite in the transverse normal-longitudinal shear stress space is obtained and compared with Puck's model. The results show that both interfaces with low fracture toughness and microvoids with even small void volume fraction can significantly reduce the macroscopic strength of composite. The size and shape of microvoids can also microscopically lead to different crack paths.